Evaluasi Pemikiran Qasim Amin tentang Emansipasi Wanita dalam Islam - Achmad Tohari; Dian Pramodya Cahyani (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2021)
The idea of ​​women's emancipation is a manifestation of Qasim Amin's concern about the reality of Egyptian women who are still far under the domination of men. This literature research attempts to analyze the thoughts of Qasim Amin – who is also an Egyptian reformer – in a broader perspective with relevant sources. Furthermore, the author evaluates his thoughts in the frame of modern Islamic education. This research finds that according to Qasim Amin, Egyptian women are no longer about their relationship with men, but also about sociological and independent rights as individuals who are already tied to traditional beliefs and patriarchal practices in the name of religion are fairly well established. From the thoughts of Qasim Amin, it will be directed to the problem of women in the world of education that is currently happening, where women are included or can make changes to the times. In the context of Islamic education, Qasim Amin's thoughts can develop democratic thinking by forming akhlaq al-karimah that is in accordance with the ability of reason and the context of universal humanity.